University students' attitudes about online mathematics teaching during the pandemic - Mihajlović Aleksandra M.; Ristić Vladimir T.; Kopas-Vukašinović Emina M. (Zbornik radova (Univerzitet u Kragujevcu. Pedagoški fakultet u Užicu))
The COVID-19 pandemic forced universities all over the world to shift from face-to-face to online education. Teaching and learning mathematics online bring many challenges for teachers due to its heavily symbolic and diagrammatic nature. The aim of the study was to determine whether it is possible to achieve good quality of university students' work and effectiveness of teaching by organizing online mathematics classes at non-mathematical faculties in the Republic of Serbia. The research focused on exploring students' views of online mathematics teaching, considering the influence of educational-scientific fields of their study programs and self-assessed level of mathematical knowledge. The study was conducted among undergraduate students (N = 224) of seven faculties/ departments of three state universities and one private university in 2022. Both quantitative and qualitative methods were used for data analysis. The research results point to the conclusion that undergraduate students from our sample generally did not express positive attitudes towards online mathematics classes. Also, their attitudes were determined by the educational-scientific fields of the study programs they studied, as well as by their self-assessment of mathematical knowledge. Such results can be a significant starting point for new research on the quality and effectiveness of teaching, which should includeuniversity teachers who organized online mathematics classes.